2005
DOI: 10.1074/jbc.m413307200
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of Exocytotic Sites by the Formation of Phosphatidylinositol 4,5-Bisphosphate Microdomains at Syntaxin Clusters

Abstract: Phosphatidylinositol 4,5-bisphosphate (PI(4,5)P 2 ) is a minor component of the lipid bilayer but plays an important role in various cellular functions, including exocytosis and endocytosis. Recently, PI(4,5)P 2 was shown to form microdomains in the plasma membrane. In this study, we investigated the relationship between the spatial organization of PI(4,5)P 2 microdomains and exocytotic machineries in clonal rat pheochromocytoma PC12 cells. Both PI(4,5)P 2 and syntaxin, a soluble N-ethylmaleimide-sensitive fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
203
5
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(223 citation statements)
references
References 52 publications
10
203
5
2
Order By: Relevance
“…With additional control parameters (i.e., osmotic pressure, temperatature, composition) a transition to a nonlamellar states is then easily induced. In this context, we also found that the lipid phosphatidylinositol-4,5-bisphosphate (PIP 2 ), which is enriched at the sites of vesicle fusion of synaptic membranes (84,85), has a very pronounced effect on the phase behavior of DOPC and promotes stalk and inverted hexagonal phase formation already at concentrations of few mol% (43). As a strongly anionic lipid with three net negative charges, PIP 2 is likely to interact with Ca 2þ , possibly again facilitating localized dehydration and hydrophobic defect formation.…”
Section: Discussionmentioning
confidence: 88%
“…With additional control parameters (i.e., osmotic pressure, temperatature, composition) a transition to a nonlamellar states is then easily induced. In this context, we also found that the lipid phosphatidylinositol-4,5-bisphosphate (PIP 2 ), which is enriched at the sites of vesicle fusion of synaptic membranes (84,85), has a very pronounced effect on the phase behavior of DOPC and promotes stalk and inverted hexagonal phase formation already at concentrations of few mol% (43). As a strongly anionic lipid with three net negative charges, PIP 2 is likely to interact with Ca 2þ , possibly again facilitating localized dehydration and hydrophobic defect formation.…”
Section: Discussionmentioning
confidence: 88%
“…Recent studies have shown that vertebrate CAPS-1 activity and binding to the plasma membrane of PC12 cells depend on the lipid PIP 2 (Grishanin et al 2004), which is concentrated in submicrometer-size microdomains that correlate with sites of dense-core vesicle exocytosis in PC12 and chromaffin cells (Aoyagi et al 2005;Milosevic et al 2005). Further studies will be necessary to determine whether or not UNC-31's recruitment to high focal concentrations at active zones is PIP 2 dependent.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting possibility is the PIP2-mediated regulation of Wiskott-Aldrich syndrome protein (WASP)-Arp2/3 pathway, which is required for actin nucleation 55 and for the formation of an organized cytolytic synapse 56,57 ; another possibility is the control of vesicle fusion step via PIP2 interaction with the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) factor syntaxin, as reported in other secretory systems. 58 Notably, WASP and syntaxin 11 mutations are responsible for Wiskott-Aldrich syndrome 56,57 and familiar hemophagocytic lymphohistiocytosis 4 immunodeficiencies, 59 respectively, both characterized by a defective cytotoxic function. Experiments are ongoing to elucidate whether PIP2 pools are actually implicated in the regulation of actin-and SNAREdependent events in cytotoxicity.…”
Section: Org Frommentioning
confidence: 99%